Clinical Characterization of Canine Acanthomatous Ameloblastoma (CAA) in 263 dogs and the Influence of Postsurgical Histopathological Margin on Local Recurrence. (December 2017) - Goldschmidt, Stephanie L.; Bell, Cindy M.; Hetzel, Scott; Soukup, Jason
Canine acanthomatous ameloblastoma (CAA) has been reported to be the most common odontogenic tumor in dogs. This retrospective study evaluated 263 dogs with histopathologically confirmed CAA. Within this data set, CAA presents most commonly in the rostral mandible in adult large breed dogs, with golden retriever dogs being overrepresented. Patients with appropriate follow-up after curative intent surgery were evaluated to assess the effect of histopathological margin on local tumor recurrence. No local recurrence was noted in any patient. This study raises questions about what the recommended surgical margin should be for treatment of CAA. It also serves as a stimulus for discussion as to whether further treatment for CAA is required when inadequate surgical margins are obtained, or if medical surveillance would be an appropriate management recommendation. Prospective studies are necessary to answer these questions.